LIVELIHOOD STRATEGIES OF FISHING LABOR HOUSEHOLDS IN AIR BANGIS VILLAGE, WEST SUMATRA - Yulianda, Egi; Irwan, Irwan; Erningsih, Erningsih (Universitas Tanjungpura, 2023)
This research was conducted by fishermen who experienced economic problems in household life, where the income earned by fishermen was not sufficient to meet their daily needs, even the UMP they brought. West Sumatra. The average income of fisherman workers is Rp. 1,000,000. per month, but there are still fishermen who still survive as traditional fishermen. Even though work as a fisherman is a big risk and has an erratic income. The theory used in this study is the subject strategy theory put forward by White 1991. The approach used in this research is a qualitative approach with a descriptive type. Retrieval of informants using purposive sampling with a total of 7 informants, 1 Jorong Pasar Muara and 6 fishermen Jorong Pasar Muara. There are two types of data in this study, namely primary data and secondary data. The research data was collected using observation techniques, interviews and document studies. Data analysis uses Miles and Huberman's thinking by collecting data, reducing data, presenting data and drawing conclusions using the unit of analysis in this study are individuals. The results of the study show that work as a fisherman is the main occupation of the Jorong Pasar Muara household, fisherman workers continue to work so that they can fulfill the household economy.